2020
DOI: 10.1097/sla.0000000000004497
|View full text |Cite
|
Sign up to set email alerts
|

Underemployment of Female Surgeons?

Abstract: Objective: To compare the complexity of operations performed by female versus male surgeons. Background: Prior literature has suggested that female surgeons are relatively underemployed when compared to male surgeons, with regards to operative case volume and specialization. Methods: Operative case records from a large academic medical center from 1997 to 2018 were evaluated. The primary end point was work r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 13 publications
2
34
2
1
Order By: Relevance
“…For example, if female trainees feel they have lower levels of operative autonomy during residency or fellowship, they might feel less prepared to perform more difficult procedures after graduation, a hypothesis supported by a recent study in which female attending general surgeons performed less complex cases than male colleagues even when controlling for subspecialty and seniority. 22 Lastly, we found that female trainees logged fewer complex cases than their male colleagues, which warrants further exploration and possible intervention. If female trainees were actually performing fewer difficult cases because they were assigned to or volunteered for them, programs should increase oversight to ensure even allocation of complex cases.…”
Section: Discussionmentioning
confidence: 70%
“…For example, if female trainees feel they have lower levels of operative autonomy during residency or fellowship, they might feel less prepared to perform more difficult procedures after graduation, a hypothesis supported by a recent study in which female attending general surgeons performed less complex cases than male colleagues even when controlling for subspecialty and seniority. 22 Lastly, we found that female trainees logged fewer complex cases than their male colleagues, which warrants further exploration and possible intervention. If female trainees were actually performing fewer difficult cases because they were assigned to or volunteered for them, programs should increase oversight to ensure even allocation of complex cases.…”
Section: Discussionmentioning
confidence: 70%
“…Even within well-paid occupations, there are gender gaps that can be partially explained by the prestige and gendered social expectations of each subfield. For example, despite the increase in the number of female doctors overall, relatively few women still practice surgery, especially complex surgery [82].…”
Section: Related Workmentioning
confidence: 99%
“…The gender variable has been associated with adverse implications while choosing the surgical eld, training for residency programs, and daily working in medical practice [13][14][15]. When appraising the intersections with minorities based on race, sexuality, and socioeconomic class, the gap expands [14,16,17]. In this sense, GEIGS general assembly had capacity-building as a core value for its members and external participants.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…For example, existing supportive bene ts, like parental leave, and mechanisms to report discrimination play a vital role in retaining these groups in the SOA elds [15]. Along with these strategies, promoting diversity and putting women and non-binary people in leadership helps to mitigate the pipeline effect [16,18]. The "leaky pipeline" effect describes a precipitous decline in women compared with men at each progressive step in the academic ladder, in which women occupy less leadership roles such as faculty, division chiefs, full professors, department chairs, and deans [18,19].…”
Section: Policy Implicationsmentioning
confidence: 99%